The effectiveness of b-lynch sutures in management of atonic postpartum haemorrhage during caesarean section - Kalkal, Nidhi; Sarmalkar, Meenal S.; Nayak, Arun H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Surgical methods of controlling uterine bleeding by inserting compression sutures have been developed to reduce the incidence of emergency hysterectomy and to preserve fertility in patients with atonic postpartum haemorrhage (PPH). The aim of the study was to determine the efficacy of B-Lynch suture in management of atonic PPH and to determine whether timely application of B-Lynch suture in uncontrolled atonic PPH obviates the need for hysterectomy and thus help in pursuing subsequent fertility. Methods: A prospective observational study of 30 patients who underwent B-Lynch suturing for atonic PPH during lower segment cesarian section (LSCS), refractory to medical line of management was conducted. The amount of blood loss, need for blood transfusion and hysterectomy were noted. The patients were followed-up for 6 months for any late postoperative complications and for any infertility issues. Results: The procedure was successful in 100% of the cases following failure of medical line of management. None of them required hysterectomy or uterine devascularisation. All patients had uneventful puerperium. No evidence of ischemic necrosis or pyometra on assessment of patients on 6 month follow up. Conclusions: This procedure proves to be a valuable addition for surgical treatment of atonic PPH and great advantage in young patients with restoration of future fertility with the added advantage of lesser time of application, lesser blood loss, lesser blood transfusion, lesser skill required. Thus, B-Lynch suturing can be adopted as a mid-step before resorting to uterine devascularisation or hysterectomy when medical line of management fails.